Keragaman genetik Anggrek Grammatophyllum scriptum asal biji dari hasil Kultur In Vitro berdasarkan penanda RAPD - Zarima Wibawati; Amelia Sarungallo; Barahima Abbas (Cassowary, 2021)
Propagation through tissue culture by using orchid seed as explants will produce a lot of orchid plants. This study aims to measure the genetic character of orchid plantlets that were regenerated from seeds which have been resulted from in vitro culture. The genetic character of the original orchid plants produced from in vitro culture was determined using Random Amplified Polymorphic DNA (RAPD) molecular markers. The results showed that the primers used in the RAPD analysis showed a polymorphic band pattern of 14 DNA bands, with sizes between 500 bp - 8000 bp. The genetic distance of Grammatophyllum scriptum orchids that was regenerated from seeds is between 0.229 and 0.649. The progenis produced from in vitro culture were clustered into seven groups at a dissimilarity coefficient of 45%.